PENGARUH CURRENT RATIO, RETURN ON ASSET DAN PRICE EARNING RATIO TERHADAP HARGA SAHAM PT.KALBE FARMA Tbk - Nur Puji Astuti (Jurnal Ekonomi dan Industri, 2021)
This type of research uses quantitative research. The data source of this research is secondary data. The data analysis method used is the correlation test, determination test, multiple linear regression test and hypothesis testing, namely the f test and t test. The results of this study indicate that the Current Ratio, Return on Assets, and Price Earning Ratio simultaneously have a significant effect on stock prices. Partially Current Ratio and Return on Asset have no significant effect, while Price Earning Ratio partially has a significant effect on the stock price of PT Kalbe Farma Tbk. To obtain this data, researchers used the website of PT Kalbe Farma Tbk, and the Indonesia Stock Exchange (IDX).